2021
DOI: 10.1101/2021.01.18.21249433
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The burden of nosocomial covid-19: results from the Wales multi-centre retrospective observational study of 2518 hospitalised adults

Abstract: ObjectivesTo define the burden of nosocomial (hospital-acquired) novel pandemic coronavirus (covid-19) infection among adults hospitalised across Wales.DesignRetrospective observational study of adult patients with polymerase chain reaction (PCR)-confirmed SARS-CoV-2 infection between 1st March – 1st July 2020 with a recorded hospital admission within the subsequent 31 days. Outcomes were collected up to 20th November using a standardised online data collection tool.SettingService evaluation performed across 1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…The methods and data sources relating to this work are described in detail elsewhere. 4 Briefly, positive SARS-CoV-2 PCR results recorded between 1 March 2020 and 1 July 2020 in adults with a recorded hospital admission were identified for retrospective notes review. Local clinical teams across 18 centres (online supplemental file S1) performed data entry using a standardised online tool.…”
mentioning
confidence: 99%
“…The methods and data sources relating to this work are described in detail elsewhere. 4 Briefly, positive SARS-CoV-2 PCR results recorded between 1 March 2020 and 1 July 2020 in adults with a recorded hospital admission were identified for retrospective notes review. Local clinical teams across 18 centres (online supplemental file S1) performed data entry using a standardised online tool.…”
mentioning
confidence: 99%
“…This mortality is much higher than the one found in other studies, 29 50 however, the similar mortality between both waves has been reported elsewhere as well. 29 The higher mortality in PHA patients than patients with community-acquired COVID-19 is also shown in recent studies, 50 although some literature has provided conflicting results. The data presented indicate that PHA infections were common during the outbreak.…”
Section: Discussionmentioning
confidence: 83%
“…A further 48 studies were excluded as they did not report mortality within both community and nosocomial-acquired COVID-19 patient groups. This left 21 studies for primary meta-analysis (9)(10)(11)(12)(13)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46), summarised in…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…We screened study quality through self-identified use of reporting standards. Three (14%) reports referenced the STrengthening the Reporting of OBservational studies in Epidemiology (STROBE) statement (9,12,36). Tables 2-4 show the formal risk of bias assessments.…”
Section: Risk Of Bias In Studiesmentioning
confidence: 99%
See 1 more Smart Citation